The Mathematical Model Analysis in Solving Two Variable Inequalities in Contextual Problems - Anisha, Ridha; Nurhaswinda; Aulya Ramadhni; Nurfaizah; Nurhamidah; Rahma Almushia; Safina Azzahara (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the use of mathematical models in solving two-variable linear inequality problems (2VLI) related to real-life situations through contextual problems. The research method used is library research, reviewing various written sources such as scientific journals, mathematics textbooks, and relevant academic publications. The analysis is conducted through five stages: problem identification, variable definition, mathematical model formulation, inequality solving, and result interpretation. The findings of the study show that the application of 2VLI mathematical models can help simplify real-life problems into systematic and structured mathematical forms. Additionally, the use of these mathematical models enhances students' conceptual understanding, critical thinking skills, and problem-solving abilities. Therefore, two-variable linear inequalities play an important role in mathematics learning, especially in linking mathematical concepts to real-life contexts.